Media content's role in the making of a democrat: Evidence from East Germany - Tim Friehe; Helge Müller; Florian Neumeier (Philipps-University Marburg, School of Business and Economics, 2017)
This paper explores the causal influence of access to Western television programming on voting behavior. We exploit a natural experiment involving access to West German TV within the German Democratic Republic in which only geography and topography determined the allocation of individuals to treatment and control groups. Focusing on both the shares of extremist parties and voter turnout, we find that in the post-reunification decade in which TV content was harmonized, regions that already had access to Western TV broadcasts before reunification experience lower vote shares of extremist parties and higher voter turnout.
Keywords: J22; K42; P37; P39; 330; Voting; Television; Media; Natural experiment; Germany